Evaluation of Ovarian Stromal Microvascularity and Clinical-Hormonal Associations in Reproductive-Aged Women with Polycystic Ovary Morphology - Hakan Baş; Süleyman Filiz (Diagnostics)
Background/Objectives: This study aims to assess ovarian stromal vascularity using microvascular imaging in reproductive-aged women with polycystic ovarian morphology (PCOM) and to explore its associations with endocrine parameters and polycystic ovary syndrome (PCOS) phenotypes. Methods: We conducted a retrospective, single-center study between January 2021 and November 2023. Women aged 18–49 who met the PCOM criteria (≥20 follicles measuring 2–9 mm or an ovarian volume >10 cm3 in at least one ovary) were included. Pelvic ultrasound with MV-Flow Doppler imaging was used to quantify the stromal vascularity index (VI). On the same day, serum levels of FSH, LH, total and free testosterone, DHEAS, and estradiol were measured. PCOS phenotypes (A, C, D, and non-PCOS) were classified according to the Rotterdam criteria. Statistical analysis involved interobserver agreement using intraclass correlation coefficients (ICCs), correlation analysis for hormonal associations, and group comparisons using ANOVA. Results: A total of 111 women (mean age: 27.4 ± 6.1 years) were evaluated. The mean VI was 43.88 ± 19.84, with good interobserver agreement (ICC = 0.79; 95% CI: 0.65–0.88). VI was highest in Phenotype A (61.36 ± 10.11), followed by Phenotype C (42.57 ± 3.59), Phenotype D (26.47 ± 4.24), and Non-PCOS individuals (9.95 ± 5.44; p < 0.001). VI showed strong positive correlations with total testosterone (r = 0.797) and free testosterone (r = 0.778), and a moderate negative correlation with DHEAS (r = −0.483; p < 0.001). Conclusions: Microvascular imaging is a promising tool for quantifying ovarian stromal vascularity in PCOM. Its strong correlation with androgen levels, especially in hyperandrogenic phenotypes, highlights its potential role in enhancing diagnostic precision and deepening our understanding of PCOS pathophysiology.